PENGARUH KUALITAS AUDIT, OPINI AUDITOR, PROFITABILITAS TERHADAP AUDIT REPORT LAG DENGAN UKURAN DEWAN KOMISARIS SEBAGAI VARIABEL MODERASI - Artrisca Tya Luxviasah; Andy Dwi Bayu Bawono (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to determine the influence of audit quality, audit opinion, and profitability on the delay in issuing audit reports, while considering the size of the board of commissioners as a moderating variable. The study is conducted on manufacturing firms that are publicly traded on the Indonesian Stock Exchange from 2019 to 2021. Purposive sampling procedures were employed, resulting in a sample size of 378. The research incorporates three independent variables, namely audit quality, audit opinion, and profitability. The study employs dummy variables to assess the audit quality, a dummy variable to represent the auditor's viewpoint, and the return on asset ratio (ROA) to measure profitability. The audit report lag is the dependent variable utilized. The findings of this study indicate that the audit report is delayed by the quality of the audit, the auditor's viewpoint, and profitability. The moderating effect of board of commissioners size on the link between audit quality and audit lag report is not significant.